Pipeline Embolization Device for Pericallosal Artery Aneurysms: A Retrospective Single Center Safety and Efficacy Study - De Macedo Rodrigues, Katyucia; Kühn, Anna Luisa; Tamura, Takamitsu; Dabus, Guilherme; Kan, Peter; Marosfoi, Miklos G; Lozano, J Diego; Perras, Mary; Brooks, Christopher; Howk, Mary C; Hou, Samuel Y; Rex, David E; et al. (Operative neurosurgery (Hagerstown, Md.), 2018)
Abstract BACKGROUND Pericallosal artery aneurysm treatment may be challenging using traditional endovascular techniques. OBJECTIVE To demonstrate the feasibility, efficacy, and safety of endovascular treatment of pericallosal artery aneurysm using flow diverters. METHODS We performed a retrospective review of our institutional database from July 2013 through July 2016 and identified 7 subjects with a pericallosal artery aneurysm treated with the Pipeline embolization device (ev3 Neurovascular, Medtronic, Dublin, Ireland) and at least 1 follow-up angiogram. Technical feasibility, procedural complication, angiographic results, and clinical outcome were evaluated. RESULTS Placement of the Pipeline embolization device was successful in all cases without evidence of procedural complication. Five out of 7 subjects showed a complete aneurysm occlusion at 6- to 12-mo follow-up angiogram. The 2 subjects with persistent aneurysm filling showed decreased aneurysm sac volume on follow-up angiograms (96% and 60%). There was no evidence of in-implant stenosis or intimal hyperplasia. No thromboembolic or hemorrhagic complications were seen during the follow-up period. Only 1 patient had a transient change in Modified Rankin scale score from baseline as a result of different unrelated procedure. CONCLUSION Our preliminary results demonstrate feasibility of the use of flow diverter stent for treatment of aneurysms of the pericallosal artery with rate of aneurysm occlusion comparable to literature and without evidence of increased procedural or short-term morbidity. A long-term and larger cohort study is needed to validate our findings.